Veiksmažodžio gramatinės kategorijos ir baltų kalbos - Palmaitis, Letas (Baltistica, 1986)
Verbal grammatical categories and the Baltic languagesThe article deals with the definition and hierarchy of the verbal categories in Baltic which are the following seven: 1. Valency is a complex classificationary lexical-syntactical category showing how many actants are possible to be immediately (not expressing a circumstance) joined to the verbal predicate. Trivalent verbs are transitive because one of their possible actants may be always represented by the direct object (mótina kẽpa ##, kẽpa # šeĩmai, kẽpa dúoną #). Bivalent verbs(e. g. habendi et sentiendi) are transitive when expressing a situation not turned to the 1st actant-subject (tùri brólį but: gaĩlisi brõlio). Intransitive verbs are bivalent, when governing an indirect complement (gaĩlisi brólio), monovalent, when demanding no complement (dúona kẽpa), and zero-valent (lyja). Thus transitivity-intransitivity is a subcategory in the frame of the category of valency (A. Paulauskienė).2. (M. Mačavariani:) Version is a complex inflexional morphosyntactical category changing the verbal valency by turning the situation towards the communicant (the 1st or 2nd person) or away from him due to the interaction with the extravert (i.e. away from the communicant as in all monopersonal IE. languages) orientation of the verbal persons. Various relations of the communicant persons are reflected in the 3rd person.If a situation is turned extravert away from the 1st actant thus coinciding with the personal orientation, the verbal valency increases at least by one realized degree since either a direct complement, or a direct and an indirect complements are created: nãmas stãtomas (1 degree) → darbiniñkas stãto nãmą (2 realized degrees), or: darbiniñkas stãto nãmą žmonė́ms (3 degrees). An introvert situation is reflexive if the 1st actant coincides with the 2nd actant (prausiúosi) or with the 3rd actant (prausiúosi véidą). If a situation is turned introvert towards the 1st actant, i. e. if it becomes opposed tо the personal orientation, the valency loses one of its degrees: darbiniñkas stãto nãmą žmonė́ms → darbiniñkas stãtosi nãmą (3 → 2, reflexivization); darbiniñkas stãto nãmą → nãmas stãtomas (2 → l, conversion). Thus the reflexivization and voice (as well as causativity) are subcategories in the frame of the category of version. IE. medial voice is a reflexive which has developed a passive meaning similarly to the Slavic reflexive. In the history of version reflexivity is older than voice (not to say medium than passive).3. The Baltic aspect is a classificationary lexical-grammatical category with no specific means of morphological expression of its own (A. Girdenis, V. Žulys).4. Person is an inflectional morphosyntactical category expressed by the system of verbal forms opposed to one another in accordance with the situation related to the communicants. The 1st and 2nd person forms expressing the communicants are opposed to the 3rd person form which does not express a communicant. In almost all IE. languages this category is not connected with that of valency and the verb is monopersonal. However in some languages two persons may be simultaneously expressed in the same verbal form (cf. O. Lith. Pone neimikorok tawa ruʃtibeie BP Π 3048) which thus appears bipersonal.5. Number is an inflectional morphological category showing how many actants are joined in the situation. In respect to number forms of the Baltic 3rd person are neutral with no morphemic realization (V. Ambrazas).6. Screeve is a complex inflectional morphological category embracing different variable elements, as person, number, etc., as well as some constant elements differentiating one screeve from another, first and foremost — the relative tense of the speaker, and mood (A. Šanige). This category of the verb is analogical to the category of case of the noun. There are 21 screeve in Lithuanian, 17 in Latvian and at least 5 screeves testified in Prussian.7. Dynamicity-stativity is a classificationary lexical-grammatical category in Baltic. Dynamical are verbs expressing an action, statical verbs express a process or state. Transitive verbs are always dynamical, intransitive verbs being dynamical (including passives and reflexives) and statical. The latter are distinguished by the neutralizing of the active and the passive voice since no conversive transformation of the situation (which is not transitive!) is possible. Formally conversive intransitive verbs (as Lith. eĩna — eĩnama) are in fact medial, verbs with the active form being medio-active eĩna) and verbs with the passive form being medio-passive (eĩnama).
Keywords: veiksmažodžio gramatinės kategorijos; baltų; morfologija